Myelination in Multiple Sclerosis Lesions Is Associated with Regulation of Bone Morphogenetic Protein 4 and Its Antagonist Noggin - Kim Harnisch (International Journal of Molecular Sciences, 2019)
Remyelination is a central aspect of new multiple sclerosis (MS) therapies, in which one aims to alleviate disease symptoms by improving axonal protection. However, a central problem is mediators expressed in MS lesions that prevent effective remyelination. Bone morphogenetic protein4 (BMP4) inhibits the development of mature oligodendrocytes in cell culture and also blocks the expression of myelin proteins. Additionally, numerous studies have shown that Noggin (SYM1)—among other physiological antagonists of BMP4—plays a prominent role in myelin formation in the developing but also the adult central nervous system. Nonetheless, neither BMP4 nor Noggin have been systematically studied in human MS lesions. In this study, we demonstrated by transcript analysis and immunohistochemistry that BMP4 is expressed by astrocytes and microglia/macrophages in association with inflammatory infiltrates in MS lesions, and that astrocytes also express BMP4 in chronic inactive lesions that failed to remyelinate. Furthermore, the demonstration of an increased expression of Noggin in so-called shadow plaques (i.e., remyelinated lesions with thinner myelin sheaths) in comparison to chronically inactive demyelinated lesions implies that antagonizing BMP4 is associated with successful remyelination in MS plaques in humans. However, although BMP4 is strongly overexpressed in inflammatory lesion areas, its levels are also elevated in remyelinated lesion areas, which raises the possibility that BMP4 signaling itself may be required for remyelination. Therefore, remyelination might be influenced by a small number of key factors. Manipulating these molecules, i.e., BMP4 and Noggin, could be a promising therapeutic approach for effective remyelination.